Strategi Komunikasi Rumah Moderasi Beragama Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember dalam Menyebarluaskan Nilai-Nilai Islam Moderat - Dzinnuroini Dzinnuroini; Ahidul Asror (Fakultas Dakwah Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2022)
Multicultural society in Indonesia, Moderation has become an important discourse. In clarifying the teachings of Islam, There are extreme views of several groups that lead to intolerance and acts of violence. So, Religious moderation known as wasathiyah, which has the equivalent of tawassuth (in the middle), i’tidal (fair) and tawazun (balanced). With the House of Religious Moderation as the frontline in guarding religious moderation thoughts and movements. So It is important to know the communication strategy of the house of religious moderation UIN KH. Achmad Siddiq Jember in spreading moderate Islamic values. This research is a qualitative descriptive study to describe the communication strategy of the religious moderation house of UIN KH. Achmad Siddiq in Disseminating Moderate Islamic values. Data collection techniques are carried out using observation, interview, and documentation owned by the Religious Moderation House, then describes the subject under study. the results of this study, that the communication strategy of the religious moderation house is in accordance with Onong Uchjana Effendy's theory of communication strategy which describes that the communication strategy is about elections (communicator) who can give messages to others either directly (face to face) or indirectly (communication through the media). This strategy is used for the communication strategy of the religious moderation house of UIN KH. Achmad Siddiq in disseminating Moderate Islamic values.